Is caffeine consumption amongst students on the rise? Comparison between medical and engineering students: a pilot study - Mehta, Sameera R.; Pokale, Aarati B.; Karmarkar, Mandar D. (International Journal Of Community Medicine And Public Health, 2018)
Background: Caffeine consumption has significantly increased over the last decade and is largely attributed to the lifestyle changes. Adverse effects of excess caffeine consumption vary from sleep disorders to dependence and withdrawal symptoms. Only a few studies are available in India regarding caffeine intake and its effects. Methods: This was a cross sectional study conducted on students of medical and engineering college students of a private university during the period from 1st October 2016 – 30th April 2017 (Seven months). Semi open ended questionnaire was administered using an online tool. The data was entered into IBM SPSS 20 USA. Percentages were calculated and chi square test was applied to find out association between Medical and Engineering student’s caffeine consumption frequency and reasons. P value <0.05 was considered significant. Results: Of 200 participants, 90 (45%) were medical students. Mean age of the participants was 20.25±1.65 years. Twelve (13.3%) medical and 17 (15.5%) engineering students consumed coffee two-three times/day. Nineteen (21.1%) medical and 19 (17.3%) and engineering students respectively consume soft drinks two-three times a week. Thirty two (35.5%) medical and 35 (29.09%) engineering students drink coffee to remain alert. Nine (10%) medical and 11 (13.8%) engineering students have unsuccessfully tried to quit coffee. Fourteen (12.7%) engineering students showed withdrawal symptoms like anxiety, restlessness and nervousness. Conclusions: Engineering students were found to be consuming more caffeine stating reason as social pastime or to increase concentration. Withdrawal symptoms like caffeine cravings, nervousness and anxiety were observed more in engineering students.